E-Waste Management on Awaring College Students - Samal, Sarat K (International Journal of Psychosocial Rehabilitation, 2019)
The point of this research paper is to know the awareness, information, discernment, and attitude of school going students about existent, hazard and the board of E-waste which is the quickly developing issues of the world. It likewise attempted to distinguish current e-waste the board rehearsed by the students. Review technique for inquire about was utilized to discover the familiarity with students in regards to E-waste the executives. A complete no of 120 students were chosen. 60 students speaking to the expert stream and 60 student speaking to the non-professional stream from various schools of University of Delhi and IP University Delhi. Basic Random examining system was utilized to gather the information. Oneself created E-Waste Management Awareness Questionnaire (EWMAQ) was utilized to gather the information. Poll was intended to ask the students how they would react to explicit e-waste related inquiries and circumstances. It was discovered that there is no noteworthy contrast in the awareness in regards to presence of E-waste in students of expert stream and non-professional streams. It implies every one of the students independent of their stream are having familiarity with existent of e-waste. However, there is critical contrast in the awareness in regards to danger of E-waste in undergrads of expert stream with their non-professional partners. It implies students of expert stream are having more consciousness of danger of e-waste than the students of non-professional stream, and students of both the streams are unaware of proper e-waste executives.